Criminal Act of Femicide in the Perspective of Human Rights: An Analysis of Law Enforcement in Indonesia - Oktadiana, Viri; Maman Suherman, Ade; Setiady, Tri (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
This study aims to analyze the enforcement of law against femicide in the context of human rights (HR) in Indonesia. The main focus of this research is to identify the obstacles faced by law enforcement officers in handling femicide cases and to assess the extent to which legal protection for femicide victims aligns with human rights principles in Indonesia. This research employs a qualitative approach with a descriptive-analytical design, collecting data through literature studies, interviews with legal practitioners, human rights activists, and an analysis of relevant legal documents. The findings indicate that the enforcement of law against femicide in Indonesia faces various challenges, such as a lack of understanding of femicide among law enforcement, the dominance of a patriarchal culture, and weak reporting and handling mechanisms for gender-based violence cases. Legal protection for femicide victims remains ineffective, despite the existence of regulations aimed at safeguarding women's rights. This research recommends the need for enhanced legal awareness, training for law enforcement, and stronger law enforcement measures to provide better protection for femicide victims in Indonesia.